Pengembangan Dakwah Pondok Pesantren Penghafal Alquran (PPPA) Raudhatul Jannah melalui Program Halal Tourism - Widagda, Sidiq Pramana; Prasetyanto, Hermawan; Yulianto, Gunawan; Rachmadi, Hari (Sekolah Tinggi Pariwisata AMPTA, 2020)
The goal and target of tourism development in 2020 is increasing image, competitiveness, and contribution of tourism in support of community welfare improvement as well as quality economic growth.This research uses the type of field research. The results of this study indicate that: PPPA Raudhatul Jannah made Halal Tourism program in improving the people's economy by providing services of tourism program by providing shelter and providing souvenirs in the form of learning Qur'an to be Tahfidz and Studying the Qur'an The increase of tourist visit provides opportunities and challenges to the tourism to develop halal tourism. Training on the development of halal tourism make boarding school as the heart of the economy by making the craft of sport tools in the form of bows and children are also some other equipment involving the surrounding community